Ectomycorrhizal flora formed by main forest trees in the Irtysh River region of central and northeastern Kazakhstan - Sarsekova, Dani (Array, 2020)
In this study, the aim was to determine and identify symbiotically living ectomycorrhizas of the main tree species forming forests in central and northeastern Kazakhstan. Surveys were conducted on the right bank of the Irtysh River in a mixed forest of Pinus sylvestris, Picea obovata and Betula pendula trees. The collection was formed and the primary identification of voucher samples of fruiting bodies of macromycetes collected as ectomycorrhiza forming fungi was completed. In the collection and species identification of fruiting bodies, standard methods were used. A total of 30 ectomycorrhizas belonging to Agaricomycetes were identified. The distribution of 30 species into families is as follows: Suillaceae (8), Russulaceae (7), Cortinariaceae (4), Boletaceae (3), Tricholomataceae (2), Amanitaceae (1), Cantharellaceae (1), Gomphaceae (1), Gomphidiaceae (1), Paxillaceae (1), and Bankeraceae (1). The richest genus on account of the number of species was Suillus (8). Concerning the woody host species, 17 mycorrhizas were determined to build symbiosis with P. sylvestris, 8 mycorrhizas with B. pendula, 6 mycorrhizas with Populus tremula, 1 mycorrhiza with P. obovata, 1 mycorrhiza with Quercus robur, 1 mycorrhiza with Salix sp., and 1 mycorrhiza with Pinus densiflora Siebold and Zuccarini. Ectomycorrhizas should be used as a major performance-enhancing tool in afforestation and restoration studies in the Irtysh River basin under extreme ecological conditions and under climate change effects.